A Study to Assess the Effectiveness of Educational Package in Terms of Knowledge Regarding Essential New Born Care among Mother in the Postnatal Wards of Selected Hospital, Nadiad - Parmar, Krupal; Parmar, Krupali; Parekh, Mansi; Parmar, Nainesh; Parmar, Niyanta; Vyas , Dhara (Journal of Ecohumanism, 2024)
BACKGROUND: The neonatal period, covering the first 28 days of life is a vital stage marked by significant physiological changes and the new borns adjustment to the crucial for the baby’s survival and long term health. Proper new born care is essential in decreasing neonatal illness and death promoting healthy growth and development. Worldwide neonatal mortality is a major public issue, especially in low and middle income nations. The World Health Organization (WHO) reports that nearly 2.4 million children die within their first month of life annually, with most of these deaths happening within the first week. Infection are a leading cause of neonatal mortality, responsible for about one-third all neonatal deaths. New born are practically vulnerable to infection due to their underdeveloped immune system. Education on essential new-born care, covering aspects like infection prevention, breastfeeding thermal care, and immunization, plays a critical role in decreasing these fatalities. Postnatal wards offer a special chances to educate mothers about essential new-born care. During this period mothers are typically more open to learning and incorporating new practice that can benefit their infants. Tailored educational programs designed for postnatal mothers of essential new-born care practice and encourage their adoption. AIM This study assess the effectiveness of an educational package design to enhance mothers’ knowledge regarding essential new born care in selected hospital in Nadiad. OBJECTIVE: To evaluate the impact of an educational package on mothers’ knowledge about essential new born care in post natal wards. METHODS A quasi experimental study design was employed. The study include 40 mothers in post natal wards from selected hospital in Nadiad. Participants were divided into two groups: An experimental group receiving the educational package and a control group receiving standard care. Pre-test and post- test knowledge assessments were conducted using a structured questionnaire. INTERVENTION: The educational package comprised informative flip book interactive session focus on essential new born care such as breast feeding, hygiene, immunization and recognizing dangerous sign.RESULTS: The pre-test knowledge scores of both groups were comparable. Post intervention, the group showed a significant increase on knowledge scores compared to the pre- test. Statistical analysis using paired T test revealed that the educational package effectively improved mother’s knowledge of essential new born care (p< 0.05). The educational package significantly enhanced mother’s knowledge regarding essential new born care in post natal wards. Implementing such educational interventions can improve new born health outcomes by empowering mothers which crucial care. Further studies are recommended to assess long term retention of knowledge and its impact on new born health.